1994
DOI: 10.1176/ajp.151.2.190
|View full text |Cite
|
Sign up to set email alerts
|

Short-term psychotherapy of personality disorders

Abstract: These data indicate that brief adaptive psychotherapy and short-term dynamic psychotherapy are effective for patients with certain types of personality disorder and that the two therapy approaches do not differ in overall outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(25 citation statements)
references
References 15 publications
0
25
0
Order By: Relevance
“…Yet, several previous studies showed that specialised psychotherapeutic treatment yields better outcomes than various control conditions (for example waiting list controls) [8,9,13]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, several previous studies showed that specialised psychotherapeutic treatment yields better outcomes than various control conditions (for example waiting list controls) [8,9,13]. …”
Section: Discussionmentioning
confidence: 99%
“…[7]], the available studies on cluster C PD typically compare treatments that are identical in treatment setting and duration. Investigators have compared different outpatient treatments [8,9,10,11,12,13], different day hospital treatments [14,15], and different inpatient treatments [16,17]. One recent study in Norway [18] compared outpatient and day hospital treatment for patients with all forms of PD, and found no significant superiority of one treatment over another at 8 months after the start of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Although several findings may indicate the efficacy of ‘specific factors’ in brief dynamic psychotherapy (BDT) [1, 2, 3, 4, 5], these treatment techniques have rarely been studied systematically as treatment for depressive disorders. Several authors who studied the efficacy of BDT in combined treatment with antidepressants reported a higher improvement compared to pharmacological monotherapy [6, 7].…”
Section: Introductionmentioning
confidence: 99%
“…Their study sample also included patients with paranoid PD (n = 4) and schizoid PD (n = 5), but their results were not reported separately. The same holds true for the small group of cluster A PD patients (n = 4) in a study of Winston et al [36]. On the other hand, Gude and Vaglum [37] in their study on inpatients found no differences in improvement of psychiatric symptoms and occupational status between pure cluster A PD patients (n = 21) and both pure cluster B and pure cluster C patients.…”
Section: Introductionmentioning
confidence: 64%